2019
DOI: 10.1002/ente.201901218
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐Metal (Zn, Mn) Metal–Organic Framework–Derived ZnMnO3 Micro‐Sheets Wrapped Uniformly with Polypyrrole Conductive Network toward High‐Performance Li‐Ion Batteries

Abstract: Recently, porous mixed metal oxides have drawn interest as advanced anodes toward Li‐ion batteries (LIBs). However, there are existing challenges in achieving high‐rate capacities/cycle stabilities in practical applications. Herein, bottom‐up solvothermal fabrication of bi‐metal (Zn, Mn) metal–organic framework (MOF)‐derived ZnMnO3 (ZMO) micro‐sheets (MSs) is first devised, which are further wrapped uniformly with flexible polypyrrole (PPY) via efficient gaseous polymerization. In the hybrid (denoted as PPY@ZM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Synthesis routes for crystalline ZnMnO 3 reported so far, in contrast, involve high temperature process steps. [14,[18][19][20][21][22][23][24][25][26] The presented synthetic approach, which is exemplified here for ZnMnO 3 /ZnO heterostructures, may possibly constitute a more general strategy for the room-temperature deposition of different ternary oxide nanostructures. While this remains to be proven, more mechanistic insights into the electrodeposition process will allow to elucidate process -as well as materialrelated prerequisites (e. g. structural and compositional properties of the involved scaffold and deposit materials) for the successful room-temperature electrodeposition of crystalline ternary oxides.…”
Section: Impact Of Substrate Morphology -Zno Nanowire Arrays Versus R...mentioning
confidence: 99%
“…Synthesis routes for crystalline ZnMnO 3 reported so far, in contrast, involve high temperature process steps. [14,[18][19][20][21][22][23][24][25][26] The presented synthetic approach, which is exemplified here for ZnMnO 3 /ZnO heterostructures, may possibly constitute a more general strategy for the room-temperature deposition of different ternary oxide nanostructures. While this remains to be proven, more mechanistic insights into the electrodeposition process will allow to elucidate process -as well as materialrelated prerequisites (e. g. structural and compositional properties of the involved scaffold and deposit materials) for the successful room-temperature electrodeposition of crystalline ternary oxides.…”
Section: Impact Of Substrate Morphology -Zno Nanowire Arrays Versus R...mentioning
confidence: 99%
“…The diffraction peaks at 18.353, 30.272, 35.670, 43.472, 53.886, 57.322 and 62.963 were indexed to ZnMnO 3 (PDF# 19-1461). 26 The sample could match well with the cubic phase of ZnMnO 3 (PDF# 19-1461), and we were able to observe from the graph an obvious carbon peak, 27 which would preliminarily indicate that the synthesized sample was ZnMnO 3 /C, while no other peaks were observed, which indicated that the purity of the product was very high. 28 In order to further conrm the structural data of ZnMnO 3 /C, Raman spectroscopy investigation was performed (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…2f). 26 The two tting peaks for both O corresponded to the metal-oxygen bond and the hydroxyl bond at 530 and 531.4 eV, respectively (Fig. 2h).…”
Section: Resultsmentioning
confidence: 95%
“…Coating of microspheres of this material with PPy yielded an electrode material showing stable capacity retention during 200 cycles after significant losses in the initial cycles (Yang et al 2020a). Wrapping of MOF-derived microsheets of ZnMnO 3 with PPy yielded a more stable material with improved rate capability (Sun et al 2020). A coating of PANI (initially called chemisorbed PANI in the report) resulted in increased surface area and optimum porosity of Co 3 O 4 enabling a storage capability greater by 50% as compared to the uncoated oxide for use as positive electrode in a supercapacitor/battery hybrid (Izwan Misnon et al 2020).…”
Section: Auxiliary Components and Functionsmentioning
confidence: 99%